An Agroclimatic Appraisal of Moisture Stress During Kharif Season in Karnataka - Ratnam, B P; Joshi, S N (Annals of Arid Zone, 2016)
Zones of different moisture stress viz., little or insignificant, moderate: large and severe, in Karnataka, South India, for the months of June, July, August and September, were delineated according to the percentage aridity index values. There was a gradual improvement in the moisture status with the advancement of the Kharif season. In June, nearly half of the State was under large and severe moisture stress, whereas the area fell to 23 per cent in July, 14 per cent in August and nil in September.